A Proposal of Control Method Considering the Path Switching Time of SDN and Its Evaluation - Kosuke Gotani; Hiroyuki Takahira; Misumi Hata; Luis Guillen; Satoru Izumi; Toru Abe; Takuo Suganuma (Advances in Science, Technology and Engineering Systems Journal, 2019)
Recently, communication demands often change because of the various network services in companies and individuals. Software Defined Networking (SDN) has emerged as a viable control paradigm that allows flexible communication, using OpenFlow as its default standard and enabler. However, when changes happen frequently in SDN networks due to unforeseen reasons -such as a network failure or topology changes- it takes a long time to perform all the operations. For instance, to change a routing path, first new paths must be calculated, then the controller must transmit the commands to the network elements, which has to process those commands. This process can cause a delay, or even disruption, in the communication service. Therefore, this paper proposes a network control method to reduce the time to change a path using OpenFlow.
Keywords: Software Defined Network; OpenFlow; Path Switching Time